Aerosol Characterization of the Stratospheric Plume From the Volcanic Eruption at Hunga Tonga 15 January 2022. Issue 16 (23rd August 2022) - Kloss, Corinna; Sellitto, Pasquale; Renard, Jean‐Baptiste; Baron, Alexandre; Bègue, Nelson; Legras, Bernard; Berthet, Gwenaël; Briaud, Emmanuel; Carboni, Elisa; Duchamp, Clair; Duflot, Valentin; Jacquet, Patrick; et al.
Abstract: Following the Hunga Tonga eruption (20.6°S, 175.4°W, mid‐January 2022), we present a balloon‐borne characterization of the stratospheric aerosol plume one week after its injection (on 23 and 26 January 2022, La Réunion island at 21.1°S, 55.3°E). Satellite observations show that flight (a) took place during the overpass of a denser plume of sulfate aerosols (SA) compared to a more diluted plume during flight. (b) Observations show that the sampled plumes (at around 22, 25 and 19 km altitude, respectively) consist exclusively of very small particles (with radius <1 µm). Particles with radii between 0.5 and 1.0 µm show optically transparent features pointing to predominant SA. Particles with radii below 0.5 µm are partly absorbing, which could point to small sulfate coated ash particles, a feature not identified with space‐borne observations. This shows that in situ observations are necessary to fully characterize the microphysical properties of the plumes tracked by space‐borne instruments. Plain Language Summary: The Hunga Tonga‐Hunga Ha'apai volcano (at 20.6°S, 175.4°W) erupted on 13 and 15 January 2022 with injection of gases and aerosols up to 55 km altitude. Here, we present a study based on in situ aerosol observations on weather balloons on La Réunion (21.1°S, 55.3°E) within the injected Hunga Tonga aerosol plume one week after the eruption (23 and 26 January 2022). With respective satellite observations, we show that the first measurement flight took place during the overpass of a denser aerosol plume compared to the second flight. We find that the plume exhibits only small particles <1 μm, mainly consisting of sulfate aerosols (for particles between 0.5 and 1 μm in size) and an absorbing component for very small particles (<0.5 μm), possibly pointing to small ash particles coated by sulfur. This letter "absorbing" feature is a unique contribution brought by in situ measurements that fills a gap left by space‐borne instruments. Key Points: Predominant particle size range of <1 μm within the stratospheric aerosol plume of the Hunga Tonga eruption Optically absorbing particles within the plume for particles <0.5 μm point to fractured, very small ash particles Mostly optically semi‐transparent particles, for particle sizes between 0.5 and 1.0 μm result from small sulfur coated ash particles